When Money Isn’t Enough: Owner Psychological Capital as a Booster of Internal Funds for Digital Pivot Success - Sirine, Hani (Journal of Advances in Accounting, Economics, and Management, 2025)
Digital‐pivot readiness—the capability of moving commerce and operations into fully digital channels has become a survival imperative for small and medium-sized enterprises (SMEs). Yet the engines that propel this transition extend far beyond balance-sheet figures. This study unpacks the intricate triad of internal capital, external capital, and owner Psychological Capital (PsyCap—hope, efficacy, resilience, optimism), revealing how the owner’s positive mind-set converts monetary slack into digital momentum. Addressing a literature dominated by simple linear finance–performance links, we explore the transformative role PsyCap plays in re-wiring financial resources for technology adoption. Drawing on survey and audited data from 250 Indonesian SMEs across Jakarta, Surabaya, Semarang, Salatiga, and Surakarta, we employ Partial Least Squares Structural Equation Modeling (SmartPLS 4; 5,000 bootstraps). Findings show that internal capital significantly boosts digital-pivot readiness (β = 0.196, p = 0.003), whereas external capital alone remains statistically inert (β = 0.119, p = 0.074). PsyCap not only exerts a robust direct effect (β = 0.312, p < 0.001) but also acts as a psychological leverage device: it magnifies the efficacy of internal funds (interaction β = 0.087, p = 0.042) while dampening dependence on external finance (interaction β = –0.116, p = 0.047). Collectively, the model explains 48 % of the variance in digital readiness, underscoring the power of intangible resources to reconfigure tangible ones. By weaving theoretical insight with actionable guidance, this research reframes capital as psychological armour rather than mere economic fuel. For policymakers and incubators, the message is clear: pairing funding with PsyCap-building interventions—resilience coaching, strengths-based mentoring—can accelerate SME digitalization in volatile emerging markets. The study thus positions psychological well-being not as an afterthought but as the cornerstone of technological agility and long-term competitiveness.